Beneficial effects of the ketogenic diet on nonalcoholic fatty liver disease: A comprehensive review of the literature. (24th March 2020) - Watanabe, Mikiko; Tozzi, Rossella; Risi, Renata; Tuccinardi, Dario; Mariani, Stefania; Basciani, Sabrina; Spera, Giovanni; Lubrano, Carla; Gnessi, Lucio
Summary: Nonalcoholic fatty liver disease (NAFLD) is a major cause of chronic liver disease, characterized by hepatic fat accumulation and possible development of inflammation, fibrosis, and cancer. The ketogenic diet (KD), with its drastic carbohydrate reduction, is a now popular weight loss intervention, despite safety concerns on a possible association with fatty liver. However, KDs were also reported to be beneficial on hepatic pathology, with ketone bodies recently proposed as effective modulators of inflammation and fibrosis. If the beneficial impact of weight loss on NAFLD is established, less is known on the effect of macronutrient distribution on such outcome. In a hypocaloric regimen, the latter seems not to be crucial, whereas at higher calorie intake, macronutrient ratio and, theoretically, ketosis, may become important. KDs could positively impact NAFLD for their very low carbohydrate content, and whether ketosis plays an additional role is unknown. Indeed, several mechanisms may directly link ketosis and NAFLD improvement, and elucidating these aspects would pave the way for new therapeutic strategies. We herein aimed at providing an accurate revision of current literature on KDs and NAFLD, focusing on clinical evidence, metabolic pathways involved, and strict categorization of dietary interventions.